Cold water burning - Straley, John, 1953- (Straley, John, 1953- Cecil Younger mysteries., 2001)
Three years ago someone brutally killed four people on the scow Mygirl. In a crowded courtroom Cecil Younger helped the accused go free. Now the man charged with the Mygirl murders has disappeared. As a storm bears down on the Alaskan coast, two people connected with the case die in separate, sudden, and bizarre explosions of gunfire. Younger is certain that someone is trying to finish the grisly job begun on the Mygirl three years earlier. But to prove it he must chase down a wooden sloop on the wind-lashed sea. Out in the lethal storm Younger will come face-to-face with the shocking truth that has already twisted so many lives <U+2014> and now could end his own.